(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
In Economics there are two purposes to apply mathematics, one is the math- ematical tools needed to make and understand economic arguments, the sec- ond one is, to make you comfortable talking about economics using the short- hand of mathematics. The major development of the second quarter of 20th century in the field of economics was the mathematization of economics. The application of mathematical techniques to the analysis of economic problems is a methodological possibility. This technique often called as Mathemati- cal economics. Mathematics allows economists to form meaningful, testable propositions about wide-ranging and complex subjects which could less eas- ily be expressed informally. The special functions are intensively used in economic analysis to solve differential systems. Here in this paper I discussed its significant role in economic dynamics, notably in the assessment of the transition dynamics of endogenous growth models. In 2004 Boucekkine-Tamarit illustrate the Lucas-Uzawa model, which they solve by the means of Gaussian hyperge- ometric functions. They showed how the use of Gaussian hypergeometric functions allows for an explicit representation of the equilibrium dynamics of the variables in level.